Real-world experience of CPX-351 as first-line treatment for patients with acute myeloid leukemia - Rautenberg, Christina; Stoelzel, Friedrich; Roellig, Christoph; Stelljes, Matthias; Gaidzik, Verena; Lauseker, Michael; Kriege, Oliver; Verbeek, Mareike; Unglaub, Julia Marie; Thol, Felicitas; Krause, Stefan; Haenel, Mathias; et al. (Blood Cancer Journal, 2021)
To investigate the efficacy and toxicities of CPX-351 outside a clinical trial, we analyzed 188 patients (median age 65 years, range 26-80) treated for therapy-related acute myeloid leukemia (t-AML, 29%) or AML with myelodysplasia-related changes (AML-MRC, 70%). Eighty-six percent received one, 14% two induction cycles, and 10% received consolidation (representing 22% of patients with CR/CRi) with CPX-351. Following induction, CR/CRi rate was 47% including 64% of patients with available information achieving measurable residual disease (MRD) negativity (<10(-3)) as measured by flow cytometry. After a median follow-up of 9.3 months, median overall survival (OS) was 21 months and 1-year OS rate 64%. In multivariate analysis, complex karyotype predicted lower response (p = 0.0001), while pretreatment with hypomethylating agents (p = 0.02) and adverse European LeukemiaNet 2017 genetic risk (p < 0.0001) were associated with lower OS. Allogeneic hematopoietic cell transplantation (allo-HCT) was performed in 116 patients (62%) resulting in promising outcome (median survival not reached, 1-year OS 73%), especially in MRD-negative patients (p = 0.048). With 69% of patients developing grade III/IV non-hematologic toxicity following induction and a day 30-mortality of 8% the safety profile was consistent with previous findings. These real-world data confirm CPX-351 as efficient treatment for these high-risk AML patients facilitating allo-HCT in many patients with promising outcome after transplantation.
CRIS-Team WoS Importer:2021-10-15